2011
DOI: 10.1159/000331498
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Chronic Pancreatitis in Allegheny County, Pennsylvania, USA

Abstract: Background/Aims: Population-based estimates for chronic pancreatitis (CP) are scarce. We determined incident CP hospitalization rates and the risk of pancreatitis-related readmissions in Allegheny County, Pennsylvania, USA. Methods: We used Pennsylvania Health Care Cost Containment Council (PHC4) dataset to identify all unique White and Black Allegheny County residents with incident hospitalization for CP from years 1996–2005. We noted presence of alcoholism codes (from one year before index hospitalization un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…However, the correlation between the case and clinical definition is strong based on a review of patient data from our institution and is consistent with prior studies evaluating ICD-9-CM coding for AP and CP. 44,45 In addition, the distribution, size, number, location, and referral status of hospitals in the state of Maryland are similar to those from many other states. A recent study evaluating the diagnosis codes of a US-based, hospital administrative data set reported a specificity of 85% for the ICD-9-CM coding of AP.…”
Section: Discussionmentioning
confidence: 64%
“…However, the correlation between the case and clinical definition is strong based on a review of patient data from our institution and is consistent with prior studies evaluating ICD-9-CM coding for AP and CP. 44,45 In addition, the distribution, size, number, location, and referral status of hospitals in the state of Maryland are similar to those from many other states. A recent study evaluating the diagnosis codes of a US-based, hospital administrative data set reported a specificity of 85% for the ICD-9-CM coding of AP.…”
Section: Discussionmentioning
confidence: 64%
“…The risk of pancreatitis is 2–3 fold higher among Blacks than Whites 2,24 , and pancreatic cancer rates are considerably higher in Blacks than in any other racial group 9 , a disparity similar to that of lung cancer. Little is known about the reasons for the racial disparity—further research is urgently needed.…”
Section: Racementioning
confidence: 95%
“…Population-based data on CP is scarce due to its low incidence and prevalence; difficulty in establishing an early diagnosis; and, variable time course for progression from acute (AP) to CP. The overall incidence of CP (Table 1) ranges from 4.4 to 11.9 per 100,000 per year(2633). The incidence is higher in men than women by a factor of 1.5 to 3.…”
Section: Methodsmentioning
confidence: 99%